Decreased bee emergence along an elevation gradient: Implications for climate change revealed by a transplant experiment - Lindsie M. McCabe; Clare E. Aslan; Neil S. Cobb (Ecology, 2022)
Bees experience differences in thermal tolerance based on their geographical range; however, there are virtually no studies that examine how overwintering temperatures may influence immature survival rates. Here, we conducted a transplant experiment along an elevation gradient to test for climate‐change effects on immature overwinter survival using movement along elevational gradient for a community of 26 cavity‐nesting bee species in the family Megachilidae along the San Francisco Peaks, Arizona elevational gradient. In each of three years, we placed nest blocks at three elevations, to be colonized by native Megachilidae. Colonized blocks were then (1) moved to lower (warmer) elevations; (2) moved to higher (cooler) elevations; or (3) left in their natal habitat (no change in temperature). Because Megachilidae occupy high elevations with colder temperatures more than any other family of bees, we predicted that emergence would decrease in nest blocks moved to lower elevations, but that we would find no differences in emergence when nest blocks were moved to higher elevations. We found three major results: (1) Bee species moved to lower (warmer) habitats exhibited a 30% decrease in emergence compared with species moved within their natal habitat. (2) Habitat generalists were more likely than habitat specialists to emerge when moved up or down in elevation regardless of their natal life zones. (3) At our highest elevation treatment, emergence increased when blocks were moved to higher elevations, indicating that at least some Megachilidae species can survive at colder temperatures. Our results suggest that direct effects of warming temperatures will have negative impacts on the overall survival of Megachilidae. Additionally, above the tree line, low availability of wood‐nesting resources is a probable limiting factor on bees moving up in elevation.